Draft Annual Plan for 2001-2002 Volume-III Andaman and Nicobar Administration - Planning Commission (Planning Commission, 2001)
The scheme envisages to provide additional facilities in the existing ports of Andaman and Nicobar Islands and providing additional manpower by the way of creating new posts for smooth and efficient administration and operation of Ports.
Andaman and Nicobar Administration, Planning Department